Assessing the impacts of fisheries management science: a review of the Department for International Development's fisheries management science programme. - Arthur, Robert; Mees, Christopher; Halls, Ashley (Journal of Development Effectiveness, 2010)
A central objective for the UK Department for International Development (DFID)-funded research on renewable natural resource systems has been that the research commissioned results in significant positive developmental impacts. This paper examines how the DFID-funded Fisheries Management Science Programme has approached the assessment of the impact achieved through the projects it has commissioned. Fisheries pose a particular challenge for the attribution of impact and a variety of approaches to impact assessment are required, as the systems are characteristically complex, dynamic and heterogeneous. Typically fishery systems operate across multiple scales, involving a wide range of stakeholders with different, and sometimes conflicting, objectives. The paper describes the model and methods that were employed and highlights some of the developmental impact of fisheries management research achieved by projects commissioned during the 11 years of the programme. The lessons learned regarding uptake, adoption and impact assessment should be of interest both to researchers and those funding developmental research.